Academic excellence through scholarly research and publications : A multi-stakeholder perspective - Gurau, Calin (Septentrio Conference Series, 2019)
Watch the VIDEO. In the present academic world, excellence is often defined, proved and traded by using the level – both quantitative and qualitative – of scholarly research and publications realized by the staff of higher education institutions. This vision is grounded into the North American perception of academic quality, which was willingly adopted and applied by the top-ranking institutions, consequently becoming standard currency in today’s globalized academic marketplace. Although this vision has undisputable merits – especially in what concerns the capacity to clearly measure academic quality by using the number and ranking of scholarly publications, it may not always be adopted and recognized as the most desirable yardstick of organizational excellence by some stakeholders of higher education institutions. To investigate the relationship between academic excellence and scholarly research and publications, from the perspective of various stakeholder groups, we initiated in May 2018 a research project centered around the evolving research strategy of Montpellier Business School (MBS), located in the south of France. Founded in 1897, in the last 15 years MBS has known an impressive growth in the number of students and professors. Presently accredited by both the French higher education bodies, and by international institutions (AACSB, EPAS, AMBA), MBS has followed a distinctive strategy that led to a position of leader in the French market of apprentice students – students that follow their studies while working in (and being paid by) companies. In parallel, to achieve the quality standards required by national and – especially – international accreditations, the school introduced an ambitious program of increasing the number and quality of academic publications. At present, although academic quality is holistically defined and measured using three indicators (i.e., pedagogical quality, research quality, and general service), the evaluation of professors’ contribution is skewed towards research excellence. We collected primary data through face-to-face semi-structured interviews with a sample of 20 people, from each of the following categories of stakeholders: students, professors, companies. To avoid “politically correct answers” the discussions took place in informal settings, without revealing the aim of the project. The answers and the notes regarding the “non-verbal” behavior displayed by interviewees were written down immediately after the discussion, and then manually coded by the researcher, using open and axial coding techniques. The results indicate, as expected, that the perception of stakeholders regarding this topic depends on their specific interests and profiles. Although, in principle, all stakeholders outlined the importance of scholarly research and publications for knowledge creation, professional evolution, and theoretical understanding, from a practical perspective, many interviewees – especially company representatives and students – deplored the strong focus on theoretical research that has little relevance for their professional development and applications. Among some thought-provoking findings is the opinion that a good researcher is often a poor teacher, in direct relation to the level of his/her publications’ ranking, and that scholarly research and publication increasingly functions as a closed hierarchical system that has lost touch with the practical questions and needs of company managers and students.